Surgical Management of Ventral Hernia in a Deoni Crossbred Cow - Ramya, N M; Kumar, D Dilip; Shivaprakash,; Bhagavantappa , B (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Hernia is defined as the protrusion of the contents of a  body cavity through a normal or abnormal opening in  the cavity’s wall, either beneath the intact skin or into another  adjacent cavity (Tyagi et al., 2020). There are several types of  hernias that can occur in cattle; however, the most common  are ventral and umbilical hernias. A ventral hernia occurs  when the intestines protrude through the abdominal wall.  Ventral hernia develops as a result of external forces or trauma  to the abdominal wall, kick, falling on blunt object, weakening  of the abdominal musculature, or rupture of the prepubic  tendon or due to heavy body weight (Frank, 1981). Type  of hernial contents depends on the site of hernia and most  commonly the contents will be intestinal loops, mesentery,  spleen or liver lobe. Diagnosis of the ventral hernia can be  done by physical palpation in standing or recumbent position  and radiography (Abdin-Bey and Ramadan, 2001
Keywords: hernias; adjacent; abdominal; Ramadan,; umbilical